Karakteristik bahasa jurnalistik pada berita utama media cnnindonesia.com - Pascal Al Farizi; Yayan Sudrajat (Asosiasi Dosen Pemerhati Pendidikan Indonesia, 2022)
The purpose of this research is to determine the characteristics of journalistic language in the headlines of CNNIndonesia.com media technology headlines. The approach in this study is a qualitative descriptive approach. The method used in this research is descriptive analysis with a qualitative approach. In collecting data using documentation and interview techniques. The research data is in the form of news sentences in which there are characteristics of journalistic language, and the source of the data comes from online news CNNIndonesia.com editorial technology. The results of the study show the use of journalistic language characteristics obtained from the main news CNNIndonesia.com editorial technology February - April 2022 edition covering a total of 44 findings of journalistic language characteristics. These characteristics are divided into 9 characteristics, consisting of Simple as many as 0 findings, Brief and Condensed as many as 4, Straightforward as many as 7 findings, Clear as many as 11 findings, Clear as many as 8 findings, Interesting as many as 12 findings, Democratic as many as 0 findings, Populist as many as 0 findings, and Logical as many as 3 findings. Keyword : Characteristics journalistic language headlines